The quantification of cattle movement in the Bushbuckridge Local Municipality, Mpumalanga, and implications for trade and disease control - Van Rooyen, Jaques (University of Pretoria, 2020)
Mini Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2019.